2018
DOI: 10.3390/jcm7120478
|View full text |Cite
|
Sign up to set email alerts
|

Map1lc3b and Sqstm1 Modulated Autophagy for Tumorigenesis and Prognosis in Certain Subsites of Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is one of the most common cancer types worldwide and can be divided into three major subsites: buccal mucosal SCC (BMSCC), tongue SCC (TSCC), and lip SCC (LSCC). The autophagy marker microtubule-associated protein light chain 3B (MAP1LC3B) and adaptor sequestosome 1(SQSTM1) are widely used proteins to evaluate autophagy in tumor tissues. However, the role of MAP1LC3B and SQSTM1 in OSCC is not fully understood, particularly in certain subsites. With a tissue microarray compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…ATG4B is the major autophagy-related protease required for activation of membrane-bound MAP1LC3-II, which is crucial for autophagosome elongation in mammalian cells. Our recent study showed that high protein levels of MAP1LC3-II puncta are linked to unfavorable DSS in TSCC but not in BMSCC [6]. In line with our present study, ATG4B expression was associated with poor DSS in TSCC patients, implying that ATG4B expression might be positively correlated with MAP1LC3-II puncta for autophagy induction and cause poor outcome in TSCC patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…ATG4B is the major autophagy-related protease required for activation of membrane-bound MAP1LC3-II, which is crucial for autophagosome elongation in mammalian cells. Our recent study showed that high protein levels of MAP1LC3-II puncta are linked to unfavorable DSS in TSCC but not in BMSCC [6]. In line with our present study, ATG4B expression was associated with poor DSS in TSCC patients, implying that ATG4B expression might be positively correlated with MAP1LC3-II puncta for autophagy induction and cause poor outcome in TSCC patients.…”
Section: Discussionsupporting
confidence: 90%
“…The TMA blocks were employed for immunohistochemistry staining as previously reported [6]. The TMA blocks were immersed in Tris-Ethylenediamine tetraacetic acid (EDTA) buffer (10 mM, pH 9.0) and boiled in a pressure boiler at 125 • C for 10 min for antigen retrieval of ATG4B and phospho-Ser383/392-ATG4B.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Microtubule-associated protein-1 light chain 3 beta ( MAP1LC3B ) is significantly associated with adverse clinicopathological outcomes in some cancer types. Liu et al found that the expression levels of MAP1LC3B and SQSTM1 in tumor tissues were higher than those in adjacent normal tissues, suggesting that MAP1LC3B promoted the tumorigenesis and drug resistance of oral squamous cell carcinoma [ 42 ]. However, contrary to the above, high LC3 expression appears to be associated with reduced non-small-cell lung cancer invasiveness [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have been concentrated on the relationship between single or a few ARGs and OSCC prognosis. For instance, Liu PF et al found the coexpression of higher MAP1LC3B and SQSTM1 was significantly associated with poor disease-specific survival and disease-free survival in OSCC patients (23). In addition, another tissue microarray analysis suggested that ATG4B, an autophagy related protease, could be a potential biomarker for diagnosis and prognosis for OSCC (24).…”
Section: Introductionmentioning
confidence: 99%